Waste Charity: Climate Change Mitigation Efforts and Green Economic Sustainability - Muhammad Zainul Abidin; Dede Aji Mardani (al-Afkar, Journal For Islamic Studies, 2025)
The increasing volume of waste has become a significant challenge in efforts to maintain environmental sustainability. This article proposes the concept of "Trash Charity" as an innovative approach to address waste management issues while encouraging active community involvement. Trash Charity integrates social, economic, and environmental values by encouraging people to donate recyclable waste as a form of charity. This concept not only aims to reduce waste but also empowers communities through the economic value of waste management. This approach involves collaboration among communities, religious institutions, non-governmental organizations, and local governments to create a sustainable system. By emphasizing the importance of education and public awareness, the Trash Charity model has proven effective in increasing community participation, generating social benefits, and supporting the circular economy. The article also presents case studies and empirical data that demonstrate the positive impact of implementing this concept in various regions. Ultimately, Trash Charity offers a practical and ethical solution to waste problems, creating added value for the environment and strengthening social solidarity. This study recommends further development of this model for broader application as part of a national waste management strategy.